FLCN intragenic deletions in Chinese familial primary spontaneous pneumothorax. (21st March 2015) - Ding, Yibing; Zhu, Chengchu; Zou, Wei; Ma, Dehua; Min, Haiyan; Chen, Baofu; Ye, Minhua; Pan, Yanqing; Cao, Lei; Wan, Yueming; Zhang, Wenwen; Meng, Lulu; et al.
<x xml:space="preserve">Abstract</x> Primary spontaneous pneumothorax (PSP) is a significant clinical problem, affecting tens of thousands patients annually. Germline mutations in the FLCN gene have been implicated in etiology of familial PSP (FPSP). Most of the currently identified FLCN mutations are small indels or point mutations that detected by Sanger sequencing. The aim of this study was to determine large FLCN deletions in PSP families that having no FLCN sequence‐mutations. Multiplex ligation‐dependent probe amplification (MLPA) assays and breakpoint analyses were used to detect and characterize the deletions. Three heterozygous FLCN intragenic deletions were identified in nine unrelated Chinese families including the exons 1–3 deletion in two families, the exons 9–14 deletion in five families and the exon 14 deletion in two families. All deletion breakpoints are located in Alu repeats. A 5.5 Mb disease haplotype shared in the five families with exons 9–14 deletion may date the appearance of this deletion back to approximately 16 generations ago. Evidences for founder effects of the other two deletions were also observed. This report documents the first identification of founder mutations in FLCN, as well as expands mutation spectrum of the gene. Our findings strengthen the view that MLPA analysis for intragenic deletions/duplications, as an important genetic testing complementary to DNA sequencing, should be used for clinical molecular diagnosis in FPSP. © 2015 Wiley Periodicals, Inc.